Sympathetic Nervous Regulation of Calcium and Action Potential Alternans in the Intact Heart - Winter, James; Bishop, Martin J.; Wilder, Catherine D. E.; O'Shea, Christopher; Pavlovic, Davor; Shattock, Michael J. (Frontiers in Physiology, 2018)
Rationale - Arrhythmogenic cardiac alternans are thought to be an important determinant for the initiation of ventricular fibrillation. There is limited information on the effects of sympathetic nerve stimulation (SNS) on alternans in the intact heart and the conclusions of existing studies, focused on investigating electrical alternans, are conflicted. Meanwhile, several lines of evidence implicate instabilities in Ca handling, not electrical restitution, as the primary mechanism underpinning alternans. Despite this, there have been no studies of SNS on Ca alternans in the intact heart. The present study sought to address this, by application of voltage and Ca optical mapping for the simultaneous study of APD and Ca alternans in the intact guinea pig heart during direct SNS. Objective – To determine the effects of SNS on APD and Ca alternans in the intact guinea pig heart and to examine the mechansism(s) by which the effects of SNS are mediated. Methods and Results - Studies utilised simultaneous voltage and Ca optical mapping in isolated guinea pig hearts with intact innervation. Alternans were induced using a rapid dynamic pacing protocol. SNS was associated with rate-independent shortening of action potential duration (APD) and the suppression of APD and Ca alternans, as indicated by a shift in the alternans threshold to faster pacing rates. Qualitatively similar results were observed with exogenous noradrenaline perfusion. In contrast with previous reports, both SNS and noradrenaline acted to flatten the slope of the electrical restitution curve. Pharmacological block of the slow delayed rectifying potassium current (IKs), sufficient to abolish IKs-mediated APD-adaptation, partially reversed the effects of SNS on pacing-induced alternans. Treatment with cyclopiazonic acid, an inhibitor of the sarco(endo)plasmic reticulum ATPase, had opposite effects to that of SNS, acting to increase susceptibility to alternans, and suggesting that accelerated Ca reuptake into the sarcoplasmic reticulum is a major mechanism by which SNS suppresses alternans in the guinea pig heart. Conclusions – SNS suppresses cardiac alternans in the intact guinea pig heart by an action mediated through accelerated Ca handling and via increased IKs.